Revealing conducting filament evolution in low power and high reliability Fe3O4/Ta2O5 bilayer RRAM. (November 2018) - Chang, Chia-Fu; Chen, Jui-Yuan; Huang, Guan-Min; Lin, Ting-Yi; Tai, Kuo-Lun; Huang, Chih-Yang; Yeh, Ping-Hung; Wu, Wen-Wei
Abstract: In this work, we used the polycrystalline-Fe3 O4 to improve the reliability of the Ag/Ta2 O5 /Pt resistive random access memory (RRAM). In both the Ag/Ta2 O5 /Fe3 O4 /Pt and Ag/Fe3 O4 /Ta2 O5 /Pt structures, the switching properties for these bilayer RRAMs were measured in atmosphere and vacuum environments. The results demonstrated that the humidity would affect the Ag filament formation in different environments, and the Ta2 O5 and Fe3 O4 interface in a different sequence would change the performance of the device, particularly the Forming voltage. Furthermore, the switching voltage and reliability of these bilayer RRAMs was better than single-layer RRAM device, which significantly increased endurance, especially in the Ag/Fe3 O4 /Ta2 O5 /Pt device. We also observed the conducting filament shape and evolution during Forming via in/ex-situ transmission electron microscopy (TEM) in the Ag/Fe3 O4 /Ta2 O5 /Pt system. In low humidity, the conducting filament was composed of many weak filaments in a low-resistance state (LRS), where the grain boundaries in the Fe3 O4 layer limited filament size. The results of energy dispersive spectrometry (EDS) analysis demonstrated that the filament was composed of Ag metal. This study provided detailed switching knowledge of the bilayer RRAM for improving the reliability and power consumption of the device and new design viewpoints of the RRAM structure in future applications. Graphical abstract: For the Ag/Fe 3 O 4 /Ta 2 O 5 /Pt device, we measured the electrical properties and observed the filament shape/evolution during the Forming process via in/ex-situ transmission electron microscopy (TEM). Ex-situ TEM observation showed that the CF was composed of many weak filaments to transform the device to the low-resistance state (LRS). The results of energy dispersive spectrometry (EDS) analysis showed that the filament was composed of Ag metal. In addition, the in-situ TEM observation demonstrated the whole Ag filament Forming process in high reliability Fe3 O4 /Ta2 O5 bilayer RRAM devices. fx1 Highlights: The Ag/Fe3 O4 /Ta2 O5 /Pt devices have low Forming voltage and high stability. The bilayer RRAM demonstrated that the humidity influenced the Ag + concentration. The conduction path composed of the few Ag filaments was identified by EDS analysis. We successfully observed the Ag filament evolution  via in-situ  TEM. The Fe3 O4 /Ta2 O5 bilayer device would form thinner filament than single layer device.